DNA mismatch repair deficiency and hereditary syndromes in Latino patients with colorectal cancer. Issue 19 (22nd June 2017) - Ricker, Charité N.; Hanna, Diana L.; Peng, Cheng; Nguyen, Nathalie T.; Stern, Mariana C.; Schmit, Stephanie L.; Idos, Greg E.; Patel, Ravi; Tsai, Steven; Ramirez, Veronica; Lin, Sonia; Shamasunadara, Vinay; et al.
Abstract : BACKGROUND: The landscape of hereditary syndromes and clinicopathologic characteristics among US Latino/Hispanic individuals with colorectal cancer (CRC) remains poorly understood. METHODS: A total of 265 patients with CRC who were enrolled in the Hispanic Colorectal Cancer Study were included in the current study. Information regarding CRC risk factors was elicited through interviews, and treatment and survival data were abstracted from clinical charts. Tumor studies and germline genetic testing results were collected from medical records or performed using standard molecular methods. RESULTS: The mean age of the patients at the time of diagnosis was 53.7 years (standard deviation, 10.3 years), and 48.3% were female. Overall, 21.2% of patients reported a first‐degree or second‐degree relative with CRC; 3.4% met Amsterdam I/II criteria. With respect to Bethesda guidelines, 38.5% of patients met at least 1 criterion. Of the 161 individuals who had immunohistochemistry and/or microsatellite instability testing performed, 21 (13.0%) had mismatch repair (MMR)‐deficient (dMMR) tumors. dMMR tumors were associated with female sex (61.9%), earlier age at the time of diagnosis (50.4 ± 12.4 years), proximal location (61.9%), and first‐degree (23.8%) or second‐degree (9.5%) family history of CRC. Among individuals with dMMR tumors, 13 (61.9%) had a germline MMR mutation (MutL homolog 1 [ MLH1 ] in 6 patients; MutS homolog 2 [ MSH2 ] in 4 patients; MutS homolog 6 [ MHS6 ] in 2 patients; and PMS1 homolog 2, mismatch repair system component [ PMS2] in 1 patient). The authors identified 2 additional MLH1 mutation carriers by genetic testing who had not received immunohistochemistry/microsatellite instability testing. In total, 5.7% of the entire cohort were confirmed to have Lynch syndrome. In addition, 6 individuals (2.3%) had a polyposis phenotype. CONCLUSIONS: The percentage of dMMR tumors noted among Latino individuals (13%) is similar to estimates in non‐Hispanic white individuals. In the current study, the majority of individuals with dMMR tumors were confirmed to have Lynch syndrome. Cancer 2017 . © 2017 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society . Cancer 2017;123:3732–3743. © 2017 American Cancer Society Abstract : The landscape of hereditary syndromes and clinicopathologic characteristics among Latino/Hispanic individuals in the United States with colorectal cancer remains poorly understood. Using data from the Hispanic Colorectal Cancer Study, approximately 13% of cases in the current study appear to have mismatch repair‐deficient tumors, 61.9% of which will be confirmed to have Lynch syndrome.